Problem Based Learning Methods in the Digital Era: Measuring the Impact on Students Learning Motivation and Social Character - Muhammad Fajrin Haikal; Saepul Anwar; Mohammad Rindu Fajar Islamy (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study examines the impact of the Problem-Based Learning (PBL) method on students’ learning motivation and social character development within the context of Islamic Religious Education (PAI). Reflecting Nelson Mandela’s assertion that education is the most powerful tool to change the world, fostering a supportive learning environment is especially vital in the digital era and the post-Covid-19 period, both of which have significantly affected student motivation and character formation. PBL emerges as a relevant and effective approach to meet these challenges. A mixed-methods design was employed, combining quantitative methods to measure key variables and qualitative methods for deeper insights through interviews and observations. Data collection involved 25 questionnaire items and 6 interview questions administered to educators and students, with a total of 128 survey respondents and 10 interview participants from SMAN 2 Bandung and MAN Cimahi City. Quantitative data were analyzed using descriptive statistics, while qualitative data were processed using Miles and Huberman’s framework, including data reduction, data display, and conclusion drawing. The results reveal that PBL positively influences learning motivation and supports the development of four key dimensions of social character: (1) religiosity, (2) worship, (3) responsibility, and (4) tolerance. Notably, SMAN 2 Bandung showed the greatest improvement in tolerance (3.71), whereas MAN Cimahi City excelled in the worship dimension (3.70). Overall, worship and tolerance were the most significantly affected aspects. These findings suggest that integrating PBL into PAI can enhance students' academic engagement and deepen the internalization of religious values. This study contributes empirical evidence that PBL fosters not only cognitive growth but also social and spiritual development, offering practical recommendations for educators and policymakers to create more effective, student-centered PAI learning models in a post-pandemic educational landscape.